A narrow-band coherent perfect absorption in bright–bright mode coupling metamaterials. (16th November 2016) - Hu, Xinguang; Yuan, Shuai; Armghan, Ammar; Liu, Yang; Zeng, Cheng; Jiao, Zheng; Lv, Haijiang; Huang, Ying; Huang, Qingzhong; Wang, Yi; Xia, Jinsong
Abstract: We numerically and theoretically show that a narrow-band coherent perfect absorption (CPA) can be realized in simple bright–bright mode coupling metamaterials. By adjusting the geometric parameters of metamaterial structures, the Q factor can reach 102 at 1552.8 nm with absorption exceeding 99.99%. Results show that the small resonant detuning between the two bright modes plays a crucial role in forming the CPA. Dissipation loss is responsible for tailoring the performance of CPA while the coupling strength can be used to tune the CPA resonance point to the expected wavelength. These results show the capability of metamaterials for sensors, coherence filters, modulators and ultrafast optical data processing in coherent networks.